2019
DOI: 10.1016/j.cell.2019.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Protein Sequence Editing of SKN-1A/Nrf1 by Peptide:N-Glycanase Controls Proteasome Gene Expression

Abstract: Graphical Abstract Highlights d PNGase edits glycosylated Asn residues of the SKN-1A transcription factor to Asp d These edits are required for SKN-1A to regulate proteasome subunit genes d Sequence-edited SKN-1A enhances proteostasis d Edits cause ER-targeted and cytosolic SKN-1 isoforms to regulate distinct genes SUMMARYThe proteasome mediates selective protein degradation and is dynamically regulated in response to proteotoxic challenges. SKN-1A/Nrf1, an endoplasmic reticulum (ER)-associated transcription f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
120
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(138 citation statements)
references
References 64 publications
4
120
0
Order By: Relevance
“…During this proteasome stress, NRF1 20 accumulates and is deglycosylated by NGLY1 (Tomlin et al, 2017). Rather than targeting the 21 protein for degradation, the deglycosylation activates NRF1 by converting asparagine to aspartic 22 acid residues (Lehrbach, Breen, & Ruvkun, 2019). NRF1 can then be imported into the nucleus 23 to act as a transcription factor for proteasome subunits.…”
mentioning
confidence: 99%
“…During this proteasome stress, NRF1 20 accumulates and is deglycosylated by NGLY1 (Tomlin et al, 2017). Rather than targeting the 21 protein for degradation, the deglycosylation activates NRF1 by converting asparagine to aspartic 22 acid residues (Lehrbach, Breen, & Ruvkun, 2019). NRF1 can then be imported into the nucleus 23 to act as a transcription factor for proteasome subunits.…”
mentioning
confidence: 99%
“…NGLY1 is a cytosolic deglycosylating enzyme that acts on misfolded N ‐glycoproteins destined for proteasomal degradation . Additionally, recent evidence suggested that NGLY1 is also involved in the activation of nuclear factor erythroid‐2‐like 1 (NFE2L1), a transcription factor important for stress responses . It is therefore tempting to speculate that a defect of NFE2L1 activation (or, if any, other Ngly1‐dependent molecules) might be the underlying molecular cause of the shared clinical features among these genetic disorders, as defects of either N‐ glycosylation or Ngly1 will result in defective activation of NFE2L1 (Fig.…”
Section: Liver Diseases In Cdg–a Common Mechanism With N‐glycanase 1‐mentioning
confidence: 99%
“…This common lack of NFE2L1 activation (and possibly other molecules that are activated through similar reactions) might represent the molecular mechanism underlying the similar clinical features between some CDGs and NGLY1 deficiency. Figures based on references . [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Liver Diseases In Cdg–a Common Mechanism With N‐glycanase 1‐mentioning
confidence: 99%
“…Moreover, additional homologue SKN-1A associated with the ER of Caenorhabditis elegans also mediates a cytoplasmic unfolded protein response and promotes longevity [48]. This biological event occurs to be regulated by the amino acid sequence editing of SKN-1A by NGLY1 from its glycosylated Asn (-N-S/T-) into acidic Asp (-D-S/T-) residues within this protein, in order to control expression of PSM genes against proteotoxic stress [49]. Overall, these supportive findings are prime to confirm our prior work on Nrf1 glycosylation and deglycosylation to finely tune its transactivation activity [20,33,50,51].…”
Section: Figure 7 Cross-talks From Tu Stress Signaling To Different mentioning
confidence: 99%